2013
DOI: 10.1088/1475-7516/2013/08/022
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in solid inflation

Abstract: In the model of solid / elastic inflation, inflation is driven by a source that has the field theoretical description of a solid. To allow for prolonged slow roll inflation, the solid needs to be extremely insensitive to the spatial expansion. We point out that, because of this property, the solid is also rather inefficient in erasing anisotropic deformations of the geometry. This allows for a prolonged inflationary anisotropic solution, providing the first example with standard gravity and scalar fields only … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(155 citation statements)
references
References 129 publications
5
150
0
Order By: Relevance
“…The I 2 (ϕ)F 2 models predict c 2 = c 0 /2, while primordial curvature perturbations sourced by large-scale magnetic fields generate non-vanishing c 0 , c 1 , and c 2 . Quite interestingly, in the proposed "solid inflation" scenario (Endlich et al 2013(Endlich et al , 2014; see also Bartolo et al 2013bBartolo et al , 2014Sitwell & Sigurdson 2014) bispectra similar to Eq. (23) can be generated, in this case with c 2 c 0 (Endlich et al 2013(Endlich et al , 2014.…”
Section: Directional-dependence Motivated By Gauge Fieldsmentioning
confidence: 88%
“…The I 2 (ϕ)F 2 models predict c 2 = c 0 /2, while primordial curvature perturbations sourced by large-scale magnetic fields generate non-vanishing c 0 , c 1 , and c 2 . Quite interestingly, in the proposed "solid inflation" scenario (Endlich et al 2013(Endlich et al , 2014; see also Bartolo et al 2013bBartolo et al , 2014Sitwell & Sigurdson 2014) bispectra similar to Eq. (23) can be generated, in this case with c 2 c 0 (Endlich et al 2013(Endlich et al , 2014.…”
Section: Directional-dependence Motivated By Gauge Fieldsmentioning
confidence: 88%
“…In fact, any non-Gaussianity in the form of a non-zero bispectrum will produce a correlation between a pair of modes [508,509], which implies a breaking of (statistical) translational invariance [510], and consequently of parity. This idea has been explored in [511], where it was shown that a sufficiently divergent bispectrum in the squeezed limit will couple smaller CMB modes, producing a power asymmetry in the CMB.…”
Section: Anomaly Detection: a How-to Guidementioning
confidence: 99%
“…is completely different to the physics behind the statistical anisotropy (e.g. anisotropic spacetimes [512], higher-spin (than scalar) fields [509], primordial domain walls [513], anisotropic dark energy and so on), an in-depth understanding of the physics behind the anomalies is mandatory.…”
Section: Anomaly Detection: a How-to Guidementioning
confidence: 99%
“…for any of the components of the Riemann tensor and of the vector, it is possible to obtain (21) and prove that the mean value of the energy-momentum tensor is isotropic. Thus, if oscillations are fast compared to the curvature scale, the average energy-momentum tensor takes the perfect fluid form for any locally inertial observer.…”
Section: Isotropy Theorem For Yang-mills Theories In a General Bacmentioning
confidence: 99%